The Magnetometer As A Geological Instrument At Sudbury (cadea811-3f9b-4002-abc8-81cc006519a9) - McIntosh F. Galbraith (The American Institute of Mining, Metallurgical, and Petroleum Engineers, 1942)
This paper describes the use of the magnetometer, under geological direction, in exploration of the Sudbury nickel district. The writer's experience at Falconbridge has led him to the belief that only through detailed work, and by careful correlation of both geological and geophysical results, can geophysical prospecting methods be applied successfully to mining exploration problems. It is hoped that the basic technique described in the paper will be found to have general application.